2019
DOI: 10.1038/s41598-018-38116-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomogram of hypoxia-related genes predicting overall survival of colorectal cancer–Analysis of TCGA database

Abstract: Hypoxia-related gene (HRG) expression is associated with survival outcomes of colorectal cancer (CRC). Our aim was developing a nomogram predicting CRC overall survival (OS) with HRGs and clinicopathological factors. The Cancer Genome Atlas (TCGA) database was used as discovery cohort and two Gene Expression Omnibus databases (GSE39582 and GSE41258) served as validation cohorts. A genetic risk score model prognosticating OS was developed using mRNA expression level of HRGs. Nomogram predicting OS was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Accordingly, these findings highlight a new insight into how KLK10 facilitates the development of CRC, supporting a potential avenue for the treatment of CRC. The hypoxic microenvironment is a proverbial feature of locally advanced solid tumors including CRC and constitutes a critical contributor to cancer development and survival outcomes [29,30]. Thus, we will explore the function of KLK10 in CRC cells under hypoxia conditions in our next plan.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, these findings highlight a new insight into how KLK10 facilitates the development of CRC, supporting a potential avenue for the treatment of CRC. The hypoxic microenvironment is a proverbial feature of locally advanced solid tumors including CRC and constitutes a critical contributor to cancer development and survival outcomes [29,30]. Thus, we will explore the function of KLK10 in CRC cells under hypoxia conditions in our next plan.…”
Section: Discussionmentioning
confidence: 99%
“…Geisler et al (45) found that UBE2D2-mediated autophagy is involved in the progression of Parkinson's disease. Lee et al (46) found that the expression of UBE2D2 is associated with the prognosis of patients with colorectal cancer (CRC), suggesting that UBE2D2 could be used as one of the prognostic indicators of CRC. Peng et al (47,48) argued that autophagy involved with UBE2D2 has a significant impact on the internal environment and can promote the formation and degradation of ubiquitinated aggregates through autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal is to generate simple and effective prognostic tools based on several genes and other factors that may affect RFS (10). Using the TCGA dataset, we selected 7 genes by robust likelihood-based survival modeling and built a risk score system (11). We used an independent dataset (GSE76427) to validate the effectiveness of the risk score system, demonstrating that its clinical value for predicting RFS in HCC patients is better than that of the TNM staging system.…”
Section: Given the Remarkable Development Of High-throughput Technolomentioning
confidence: 99%